John Graunt at 400: Fighting disease with numbers. Issue 4 (29th July 2020) - Harkness, Timandra
Abstract : Demographers, epidemiologists and statisticians working today are building on foundations laid by John Graunt, a London haberdasher born in 1620, who sought to analyse the many causes of death and calculate life expectancy. By Timandra Harkness Abstract : Demographers, epidemiologists and statisticians working today are building on foundations laid by John Graunt, a London haberdasher born in 1620, who sought to analyse the many causes of death and calculate life expectancy. By Timandra Harkness.